PENGEMBANGAN E-MODUL MENGGUNAKAN APLIKASI FLIPBOOK PADA MATERI PENGUKURAN LUAS PERSEGI DAN PERSEGI PANJANG - Rahma Susilowati; Irvan Permana; Nurlinda Safitri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
ABSTRACT This study aims to develop and find out the feasibility of teaching materials using flipbook applications on measuring the area of ​​a square and rectangle. This research is a Research and Development (R&D) study using the ADDIE research method (Analysis, Design, Development, Implementation, Evaluation). This research was conducted at Bantarkemang 6 Public Elementary School, Bogor City, in the 2022/2023 school year. The subjects involved in this study were four Pakuan University lecturers as flipbook media experts and language experts on measuring the area of ​​a square and rectangle, as well as two teachers at SDN Bantarkemang 6 as material experts on measuring the area of ​​a square and rectangle, and of course Class IV students. SDN Bantarkemang 6. The results of the flipbook application media expert gave a validation score to teaching materials from media expert 1 of 94.11% and media expert 2 of 87.05% included in the very feasible category, linguists measuring the area of ​​squares and rectangles gave a score validation from linguist 1 of 100% and linguist 2 of 96% is included in the very feasible category, and material expert on measuring the area of ​​a square and rectangle gives a validation score of material expert 1 of 91.66% and material expert 2 of 83.33%. And based on trials that have been carried out on class IV students as many as 25 students obtained a score of 90.54%, which means that the E-Module product using this flipbook is included in the very feasible category. It can be concluded that the development of teaching materials using the flipbook application on the material for measuring the area of ​​squares and rectangles is very appropriate for use by teachers and students in the learning process in class IV. Keywords: E-Modul, Flipbook, Mathematics